Odpowiedź :
d) 24:6×(-2)=4×(-2)=-8
24:(6×(-2))=24:(-12)=-2
e) -12+4:2-8=-12+2-8=-18
(-12+4):2-8=(-8):2-8=-4-8=-12
f) 11-8:4-10=11-2-10=-1
(11-8):(4-10)=3:(-6)=-½
Mam nadzieję, że pomogłam! ❤️
d)
[tex]24:6\cdot(-2) = 4\cdot(-2) = -8\\\\24:(6\cdot(-2)) = 24 : (-12) = -2[/tex]
e)
[tex]-12 + 4:2 - 8 = -12 + 2 - 8 = -20+2 = -18\\\\(-12+4):2-8 = (-8):2 - 8 = -4-8 = -12[/tex]
f)
[tex]11-8:4-10 = 11-2-10 = 11-12 = -1\\\\(11-8):(4-10) = 3:(-6) = -0,5[/tex]
Kolejność wykonywania działań do załączonych przykładów:
1) to, co w nawiasie,
2) dzielenie, mnożenie,
3) dodawanie, odejmowanie